Contestation of Religious Identity in the Cyber World: A Case Study of arrahmah.com and VOA Islam Dealing with Religious Others on Facebook - Mundiri, Akmal; Tohet, Moch (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2018)
Religious identity frequently causes tensions that in turn lead to social polarization. Contestation and representation of religious identity not only hit the real world but also extend to virtual communities, which are part of a new form of identity contestation in the cyber era. This study uses an ethnographic approach focusing on the beliefs, language, values, rituals, customs, and behavior of people who interact in the community as the object of research. Thus, this study portrays the phenomenon of contestation of religious identity, both in the process of forming the identity (personal identity) of members or followers. The result of this study is that there is the process of forming religious identity on Facebook i.e., in the case of arrahmah.com and VOA Islam. Such process occurs because of the awareness of personal identity, in the form of aspects that differentiate others (self-categorization) and social identity in the form of religious identity that has been internalized through the interaction process in the group. While the demographic contestation of religious identity can be categorized into primary participators as creators of content and religious mindedness narratives, and secondary participators as members who are actively involved in consuming content, and lurkers as silent participants who are targeted by propaganda. The basic form of contestation in these two communities is exclusive religious understanding and views other groups as ‘the other’.